Hematopoietic Stem Cell Transplantation in an Infant with Immunodeficiency, Centromeric Instability, and Facial Anomaly Syndrome - Gössling, Katharina L.; Schipp, Cyrill; Fischer, Ute; Babor, Florian; Koch, Gerhard; Schuster, Friedhelm R.; Dietzel-Dahmen, Jutta; Wieczorek, Dagmar; Borkhardt, Arndt; Meisel, Roland; Kuhlen, Michaela (Frontiers in Immunology, 2017)
Immunodeficiency, centromeric instability and facial anomaly (ICF) syndrome is a rare autosomal recessive genetic condition with severe immunodeficiency, which leads to lethal infections if not recognized and treated in early childhood. Up to date treatment regimens consist of prophylactic and supportive treatment of the recurrent infections. Here we report the case of a 1-year-old boy of Moroccan consanguineous parents, who was diagnosed at four months of age with ICF syndrome with a homozygous missense mutation in the DNMT3B gene. He was initially admitted to the hospital with recurrent pulmonary infections from the opportunistic pathogen pneumocystis jirovecii (PJ). Further immunological workup revealed agammaglobulinemia in the presence of B cells. After successful recovery from the PJ pneumonia, he underwent hematopoietic stem cell transplantation (HSCT) from the HLA-matched healthy sister using a chemotherapeutic conditioning regimen consisting of treosulfan, fludarabine and thiotepa. Other than acute chemotherapy-associated side effects, no serious adverse events occurred. Six months after HSCT immune-reconstitution, he had a stable chimerism with 2.9% autologous portion in the peripheral blood and a normal differential blood cell count, including all immunoglobulin subtypes. This is one of the first cases of successful HSCT in ICF syndrome. Early diagnosis and subsequent HSCT can prevent severe opportunistic infections and cure the immunodeficiency. Centromeric instability and facial anomaly remain unaffected. Although the long-term patient outcome and, the neurological development remain to be seen, this curative therapy for immunodeficiency improves life expectancy and quality of life. This case is meant to raise physicians awareness for ICF syndrome and highlight the consideration for HSCT in ICF syndrome early on.